Macrocyclic oligoesters incorporating a cyclotetrasiloxane ring - Frampton, Mark B.; Marquardt, Drew; Jones, Tim R.B.; Harroun, Thad A.; Zelisko, Paul M. (Biomacromolecules, 2015)
Macrocyclic oligoester structures based on a cyclotetrasiloxane core consisting of tricyclic (60+ atoms) and pentacycylic (130+ atoms) species were identified as the major components of a lipase-mediated transesterification reaction. Moderately hydrophobic solvents with log P values in the range of 2-3 were more suitable than those at lower or higher log P values. Temperature had little effect on total conversion and yield of the oligoester macrocycles, except when a reaction temperature of 100 °C was employed. At this temperature, the amount of the smaller macrocycle was greatly increased, but at the expense of the larger oligoester. For immobilized lipase B from Candida antarctica (N435), longer chain length esters and diols were more conducive to the synthesis of the macrocycles. Langmuir isotherms indicated that monolayers subjected to multiple compression/expansion cycles exhibited a reversible collapse mechanism different from that expected for linear polysiloxanes.